The Impact of Islamic Family Law on Women's Rights: A Comparative Study of the Shari'ah and Modern Family Laws - Erwin Hamonangan Pane; Nasution, Nur Hakima Akhirani; Harahap, Yusniar; Pulungan, Akhir Saleh (PT Inovasi Pratama Internasional, 2024)
Islamic teachings do not distinguish between the rights of women and those of men with regard to family life and social life. The Quran includes many verses on the subject of women's rights. Through textual interpretation, it can be seen that women have rights that are analogous to those of men, despite certain differences in certain areas, which can be attributed to the differing roles and responsibilities typically assumed by men. In Islam, women also possess rights similar to those of men, though certain matters differ. This discrepancy is attributed to the primary functions and responsibilities assumed by men. The following are examples of rights afforded to women in Islamic law: the right to receive an education, the right to receive a dowry and maintenance, the right to initiate divorce in instances where continuation of the marriage would result in harm, the right to inherit and the right to claim material compensation. In civil law, women's rights include: Women are accorded equal status with men with respect to their rights. In principle, women have the same freedom to pursue and obtain their rights as men, with the sole exception of married women and minors.